Research handbook on climate change and trade law - Delimatsis, Panagiotis (Edgar Elgar Publishing Ltd., 2016)
"The interaction between climate change and trade has grown in prominence in recent years. This Research Handbook contains authoritative original contributions from leading experts working at the interface between climate change and trade rules. Regional as well as international perspectives are taken into account to inform the complex questions that arise and redirect research efforts towards newly emerging issues. The Research Handbook on Climate Change and Trade Law discusses some of the most important challenges regarding conflicting interests at the intersection of trade, climate change and investment. The insightful chapters map from both regional and global perspectives the state of affairs in such diverse areas as: carbon credits and taxes, sustainable standard-setting, and trade in 'green' goods and services. This timely book redefines the interrelationship of trade and climate change for future scholarship and offers specific suggestions for much-needed research in topics such as energy, carbon taxes and credits, food, standardization, and investment. This Research Handbook will be essential reading for researchers and advanced students in international trade and investment law. It will also be an invaluable resource for practitioners and policymakers in this dynamic and highly significant area of law"--Publisher's website.